2019
DOI: 10.3349/ymj.2019.60.10.944
|View full text |Cite
|
Sign up to set email alerts
|

Various Treatment Modalities in Hepatic Hydrothorax: What Is Safe and Effective?

Abstract: PurposeHepatic hydrothorax is a complication of decompensated liver cirrhosis that is difficult and complex to manage. Data concerning the optimal treatment method, other than liver transplantation, are limited. This study aimed to compare the clinical features and outcomes of patients treated with various modalities, while focusing on surgical management and pigtail drainage.Materials and MethodsForty-one patients diagnosed with refractory hepatic hydrothorax between January 2013 and December 2017 were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…( 2 ) In another study of 41 patients with cirrhosis and HH undergoing serial thoracentesis (n = 11), pigtail drainage (n = 16), surgery (n = 10), or liver transplantation (n = 4), the 12‐month mortality rate was 18.2%, 87.5%, 70%, and 0%, respectively, for each modality. ( 86 ) One obvious limitation of this study is the small number of patients in each arm; however, the considerably lower mortality of patients in the transplant arm compared to the other groups is nonetheless striking and underscores the potentially curative role of transplant in this disease entity.…”
Section: Multidisciplinary Management Of Hhmentioning
confidence: 92%
“…( 2 ) In another study of 41 patients with cirrhosis and HH undergoing serial thoracentesis (n = 11), pigtail drainage (n = 16), surgery (n = 10), or liver transplantation (n = 4), the 12‐month mortality rate was 18.2%, 87.5%, 70%, and 0%, respectively, for each modality. ( 86 ) One obvious limitation of this study is the small number of patients in each arm; however, the considerably lower mortality of patients in the transplant arm compared to the other groups is nonetheless striking and underscores the potentially curative role of transplant in this disease entity.…”
Section: Multidisciplinary Management Of Hhmentioning
confidence: 92%
“…The presence of indwelling catheters in the pleural space in this population of patients is associated with significant morbidity and generally low rates of pleurodesis. 1 3,5,9,10,12,13 In addition, chronic and ongoing drainage can lead to malnutrition and decreased serum albumin. 11,13…”
Section: Discussionmentioning
confidence: 99%
“…1 4 Hepatic hydrothorax occurs in up to 15% of patients with end-stage liver disease, 4 is most often right-sided and is usually characterized by transudative effusions. 1,3,57 It commonly leads to minimal clinical symptoms, 1 –6 but in some it can cause significant pulmonary disease including respiratory failure. 1…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, several studies have also commented on the poor outcomes observed in patients with HH requiring intercostal chest drain insertion. Specifically, Yoon et al studied patients with refractory HH and found that the 12-month mortality of those undergoing thoracocentesis (11 patients) was 18.2%, but in those requiring pig tail drainage (16 patients), this increased to nearly 90% [47]. Further retrospective studies conducted by Orman and Lok (27 patients with HH) [48] and Liu et al (24 patients with HH) [49] reported 3-month mortality rates of approximately 40 and 27%, respectively, for those patients undergoing chest drain insertion.…”
Section: Chest Drain Insertion and Pleurodesismentioning
confidence: 99%